C-Reactive Protein Level in Admission and the Outcome of Stroke Survivors - A Ahmadi Ahangar (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Elevated CRP level is independently associated with the excessive risk of ischemic stroke. However, there is currently no consensus on the use of CRP in detecting and tracking the progression of cerebrovascular diseases. The aim of this study was to determine the relationship between CRP and outcome in stroke patients. METHODS: This was an analytical cross-sectional study. Patients admitted with diagnosis of ischemic stroke were enrolled. Demographic, and clinical characteristics, medical history, drug abuse and tobacco use and severity of stroke (National Institute of Health Stroke Scale) were completed in checklist. FINDINGS: Of the total 214 patients, the serum CRP levels in 122 cases (57%) were positive. The mortality during the first week of hospitalization included 17 cases (8%). The differences in CRP serum level with underlying disease such as Diabetes Mellitus (82 cases (51%) of positive CRP vs. 77 cases (49%) of negative CRP, p= 0.007) and Hypertension (59 cases (50.4%) of positive CRP vs. 58 cases (49.6%) of negative CRP, p=0.03) were statistically significant. In addition, high CRP was seen in 10 thrombotic (91%) and 4 embolic (67%) of stroke expire patients (p= 0.034). The difference in CRP serum level in mortality cases was statistically significant (14 cases (82%) of positive CRP vs. 3 cases (18%) of negative CRP, p= 0.032). CONCLUSION: The positive CRP serum level at the admission was accompanied by more severity of disability in stroke survivor. Checking serum level of CRP in admission is suggested for predicting disability and mortality rate during the first week of post-stroke hospitalization.